The Role of Landside and Terminal Operational Airport Officers in Supervising Facilities and Infrastructure at I Gusti Ngurah Rai Airport Denpasar Bali - Putra Denis Purnama; Elnia Frisnawati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Availability of existing and adequate facilities is a benchmark and a requirement for every airport service provider and its manager to be able to meet the needs of prospective passengers using airport services. Several fields participate in managing, maintaining, supervising the flow of passengers and goods as well as controlling terminal and landside operations, namely the AOLT (Airport Operational Landside and Terminal) unit which plays an important role in supervising and supporting the existing facilities and infrastructure at the airport so that it runs according to provisions of PM 178 of 2015 concerning "Airport Service User Service Standards". Therefore the purpose of this study is to determine the roles and constraints of AOLT (Airport Operational Landside and Terminal) officers in supervising facilities and infrastructure at I Gusti Ngurah Rai airport, Denpasar, Bali. This study uses qualitative methods, techniques in data collection through the results of observation, interviews and documentation as well as in analyzing data using data reduction, data presentation and drawing conclusions. This research was conducted at the AOLT (Airport Operational Landside and Terminal) unit at I Gusti Ngurah Rai airport, Denpasar, Bali. The results obtained from this study indicate that the role of AOLT (Airport Operations Landside and Terminal) officers in supervising facilities and infrastructure at I Gusti Ngurah Rai airport Denpasar Bali is quite good and according to what is contained in the Company's Skep and those contained in PM 178 Year 2015 concerning service standards for airport service users and standard operating procedures (SOP). However, there are still obstacles experienced by officers such as a lack of personnel or human resources (HR) and inadequate facilities.